2013
DOI: 10.1177/1947601913514851
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ect2 Nuclear RhoGEF Activity in Ovarian Cancer Cell Transformation

Abstract: Ect2, a Rho guanine nucleotide exchange factor (RhoGEF), is atypical among RhoGEFs in its predominantly nuclear localization in interphase cells. One current model suggests that Ect2 mislocalization drives cellular transformation by promoting aberrant activation of cytoplasmic Rho family GTPase substrates. However, in ovarian cancers, where Ect2 is both amplified and overexpressed at the mRNA level, we observed that the protein is highly expressed and predominantly nuclear and that nuclear but not cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 81 publications
(173 reference statements)
5
58
0
Order By: Relevance
“…Cellular fractionation revealed that RhoA and Rac1 localized to both the cytoplasm and nucleus of A549 cells, whereas Cdc42 was exclusively cytoplasmic (Figure 6A), consistent with published results (Huff et al, 2013; Lanning et al, 2003). Similar results were observed in H358 and H23 cells (Figure S5A).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Cellular fractionation revealed that RhoA and Rac1 localized to both the cytoplasm and nucleus of A549 cells, whereas Cdc42 was exclusively cytoplasmic (Figure 6A), consistent with published results (Huff et al, 2013; Lanning et al, 2003). Similar results were observed in H358 and H23 cells (Figure S5A).…”
Section: Resultssupporting
confidence: 91%
“…However, we recently showed that nuclear Ect2 GEF activity is necessary for transformed growth of ovarian cancer cells (Huff et al, 2013). We therefore generated a GEF-deficient Ect2 mutant (DH mut Ect2) (E428A and N608A within the Dbl homology (DH) domain); and NLS mut Ect2 (five key arginine residues in the Ect2 NLS changed to alanines; R348,349,350,370,372A) (Rossman et al, 2005) (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased expression and activation of these RhoGEFs result in enhanced activity of their Rho family small GTPase substrates in a context-dependent manner. For example, we recently identified overexpression of ECT2 protein in ovarian cancer, mediated by gene amplification, that resulted in activation of RHOA in the cytosol and RAC1 in the nucleus (3). The critical importance of RAC1 in cancer cell migration and invasion (4) has further focused attention on the mechanisms regulating activators of RAC1, such as the Dbl family of RhoGEFs.…”
Section: Introductionmentioning
confidence: 99%